Pengaruh Service Quality dan Fasilitas Terhadap Minat Berobat Kembali Melalui Kepuasan Pasien Sebagai Variabel Intervening di RSUD dr. Soedirman Kebumen - Parmin Parmin (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
This study aims to examine and analyze the influence of service quality and facilities on patient satisfaction and their interest in re-treatment in RSUD dr. Soedirman Kebumen. Data were collected by questionnaire using non-probability sampling and applied accidental sampling technique. This study took the sample of 100 outpatient care patients as respondents of the internish-poly of RSUD dr. Soedirman Kebumen. Data analysis techniques were using descriptive and statistical analysis techniques including validity test, reliability test, classical assumption test, hypothesis test, path analysis, and correlation analysis by using SPSS 22.0 for windows program. The results of this study indicate that all variables are valid and reliable, there is no multicollinearity and no heteroskedasticity, and the model meets the assumption of normality. The effect of the facility to patients’ satisfaction show that facility is significant to patients’ satisfactory. The effect of service quality on the interest of re-treatment shows that service quality is not significant to the interest of re-treatment. The effect of the facility on the interest of re-treatment indicated that the facility is not significant to the interest of the return of treatment. The effect of patients’ satisfaction on the interest of re-treatment shows that patient satisfaction is significant to the interest of re-treatment. Patient satisfaction is explained by service quality and facilities of 45.4% while the remaining 54.6% is influenced by other variables. Interest in re-treatment is explained by service quality, facilities, and patient satisfaction of 50.5%; while the remaining 49.5% influenced by other variables.